2019
DOI: 10.20944/preprints201904.0268.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Intellectual Capital on Economic Progress and Sustainability

Abstract: Bio-economy is a major area of the strategy that can afford the European Union to achieve growth: (i) smart, through the development of knowledge and innovation; and (ii) sustainable, based on a greener, more efficient economy in resource management. We believe that the progress of bio-economy cannot be achieved without the harnessing of intellectual capital. Our research aimed to emphasize the benefits of the dynamics of the intellectual capital growth on the evolution of the bio-economy. Thus, the informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Strong IP protection, like patents, offers protection to sustainable inventions and incentivises innovators to recoup R&D cost, but may also induce a monopoly through patenting and restrict scalability, adoption, and diffusion of sustainability-focused technologies, undermining sustainable strategies and business models when exclusivity is maintained [76,83,85]. Alongside patents, trade secrets (e.g., design secrets), copyright (e.g., software), and research data are other relevant forms of IP for green technology developers [81,82,86]. Green technology inventors may maintain trade secrets to pursue commercial development at a later time period or for business advantages [81].…”
Section: Intersection Of Ip and The Sbm: The Missing Linkmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong IP protection, like patents, offers protection to sustainable inventions and incentivises innovators to recoup R&D cost, but may also induce a monopoly through patenting and restrict scalability, adoption, and diffusion of sustainability-focused technologies, undermining sustainable strategies and business models when exclusivity is maintained [76,83,85]. Alongside patents, trade secrets (e.g., design secrets), copyright (e.g., software), and research data are other relevant forms of IP for green technology developers [81,82,86]. Green technology inventors may maintain trade secrets to pursue commercial development at a later time period or for business advantages [81].…”
Section: Intersection Of Ip and The Sbm: The Missing Linkmentioning
confidence: 99%
“…Along the innovation process, IP rights, particularly patent-related concerns for green technologies, are more common for those green technologies in commercialization stages (e.g., wind energy and hybrid cars) than those in early stages [86]. For technology development, Reichman et al [80] suggested licensing of IP and patent pools for facilitating IP sharing among green technology developers.…”
Section: Intersection Of Ip and The Sbm: The Missing Linkmentioning
confidence: 99%
See 1 more Smart Citation